Macroeconomic fluctuations in the Caribbean : the role of climatic and external shocks - Sosa, Sebastián (IMF [Washington]US, 2009)
Develops country-specific VAR models with block exogeneity restrictions to analyze how exogenous factors affect business cycles in the Eastern Caribbean. Finds that external shocks play a key role, explaining more than half of macroeconomic fluctuations in the region.